Analysis of (CAG) n Expansion in ATXN1, ATXN2 and ATXN3 in Chinese Patients With Multiple System Atrophy - Zhou, X (2018)
Multiple system atrophy (MSA) is a complex and multifactorial neurodegenerative disease, and its pathogenesis remains uncertain. Patients with MSA or spinocerebellar ataxia (SCA) show overlapping clinical phenotypes. Previous studies have reported that intermediate or long CAG expansions in SCA genes have been associated with other neurodegenerative disease. In this study, we screened for the number of CAG repeats in ATXN1, 2 and 3 in 200 patients with MSA and 314 healthy controls to evaluate possible associations between (CAG)n in these three polyQ-related genes and MSA. Our findings indicated that longer repeat lengths in ATXN2 were associated with increased risk for MSA in Chinese individuals. No relationship was observed between CAG repeat length in the three examined genes and age at onset (AO) of MSA.